Honest to God preaching : talking sin, suffering, and violence - Strawn, Brent A. (Working preacher books., 2021)
Old Testament scholar and interpreter Brent A. Strawn focuses on the importance of honesty in preaching, especially around three challenging Old Testament themes: sin, suffering, and violence. He makes the case that preaching honestly is critical in the church today. Without honesty regarding these topics, there is no way forward to reconciliation, health, and recovery. Further, it is imperative for today's preachers to deal with the questions of faith arising from these themes in the biblical text itself. In addition to key scripture passages, he turns to several contemporary authors and works as dialogue partners on the three themes. Asserting that keeping secrets can lead to a kind of sickness, Strawn uses texts from the Pentateuch and the Psalms to model honesty about sin, without which there can be no reconciliation, and honesty about suffering, without which there can be no healing. He also looks at the book of Joshua and various psalms to model honesty about violence, which can serve as a way to contain, limit, and ultimately transcend violence. Strawn frames these themes specifically for working preachers, so they can create sermons that speak to these thorny themes with depth and clarity.